Urban gardening and post-austerity in Lisbon: between subaltern urbanism and green gentrifcation - Ascensão, Eduardo (2022)
On 12th January 2020, a municipal initiative to plant 100,000 trees across Lisbon began. Several hundred people joined the efort at four locations near large public housing estates. The feel-good event drew families with young children and around 20,000 trees were planted. The following day work began on a new urban park at Praça de Espanha, a major trafc intersection where thousands of cars pass each day to and from the city centre. The latter €16 million project will connect the celebrated Gulbenkian Gardens to the Monsanto Green Corridor and is part of a broader regeneration plan for the Avenida de Berna and Praça de Espanha area, which in the next decade is expected to be consolidated into a new fnancial centre. Both initiatives are part of the Lisbon 2020 Green Capital of Europe programme, an award which has been used by the City Council as the centrepiece of Lisbon’s push to re-fashion itself as a green city. They capture the way environmental celebrations tend to oscillate between an afective, altruist dimension and a competitive one. The frst plays with people’s desire to ‘contribute as best they can’ to a better urban environment, provide simple ecological experiences for their children, and produce shaded space that reduces overall urban temperatures; the second illustrates the type of city plans associated with green growth and green gentrifcation, whereby investment on quality, sophisticated green space is part of broader plans to attract capital and reconfgure particular spaces to attract more afuent populations (Anguelovski et al., 2019) [...]